PERILAKU IBU DALAM PENYIAPAN BEKAL MAKANAN DAN SUMBANGANNYA TERHADAP KECUKUPAN GIZI ANAK TK AISYIYAH BUSTHANUL ATHFAL TANJUNG SARI MEDAN TAHUN 2014 - Hardianti Meliala; Albiner Siagian; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Preschool children have a habit to bring food every day to school. Food supplies children are generally pepared the mother of the house. Preparation of food supplies seen from the type, variety, and quantity of food. The purpose of this study is to find out the behavior of mother in the preparation of their food supplies and contribution to a child’s nutritional adequacy TK Aisyiyah Busthabul Athfal Tanjung Sari Medan in 2014. This study is a descriptive survey. The data of mothers behavior that is knowledge and attitudes which conducted by using questionnaires and interview mother preparing food supplies based on the type and amount of energy and protein consumption is obtained by food weighing their food brought to school children. The results showed that most of the mothers have a good knowledge about 88% and the mother who has a good attitude about 84% in the preparation of food supplies to children. All mother (100%) to prepare the food for children to school every day. Types of food supplies of child which is already prepared by the mothers usually a biscuit about (30%). The amount of contribution intake (52%) energy and (54%) protein in the child’s food supplies still not fill the nutritional needs of children yet. The average of contribution for food supplies of child toward the rate of nutritional adequacy provide energy contribution about 209,5 ccal (13,1%) and the protein about 5,02 g (14,3%). It is recommended to mothers to concern for the nutritional content of food given to child’s such as snack especially for the food that contain energy and protein and suggested the school to provide guidance for parents to not give or prepare their food such as snack foods to be consumed by children during recess at school. Keywords: maternal behavior, food supplies, preschooler.